Wireless Technology for Children with Autism Spectrum Disorder - Rance, Gary (Seminars in Hearing, 2014)
Autism spectrum disorder (ASD) is a neurodevelopmental condition with a range of behavioral manifestations including social interaction impairment and communication deficit. Abnormal responses to sensory stimuli across multiple modalities are commonly reported and are now a mandatory component of ASD diagnosis as specified in the Diagnostic and Statistical Manual of Mental Disorders, 5th edition. Aberrant reactions to sound were noted in Kanner's original (1943) article describing the ASD phenotype, and recent evidence has revealed that a high proportion of affected children suffer auditory processing deficits that particularly affect speech understanding in the presence of background noise. Identification and appropriate management of hearing difficulties in this population is especially important, as auditory deficits can exacerbate the communication and social problems central to the disorder. This article will review the recent literature exploring the use of wireless hearing technologies in high-functioning ASD children. Preliminary findings suggest that these systems can ameliorate auditory processing difficulties, and in so doing, enhance social interaction and improve educational outcomes for school-aged children with ASD.
Keywords: Autism spectrum disorder; auditory processing; personal FM